The use of the pronation technique in mechanical ventilation (Research, Society and Development, 2022)
The use of prone mechanical ventilation has recently been incorporated into clinical practice, after studies have shown that the loss of lung volume in supine patients with acute respiratory distress syndrome is directly related to severity. This study aimed to analyze the use of the pronation technique in patients undergoing mechanical ventilation. The study is a bibliographic research of the integrative literature review type. The search for studies was performed using the PICO strategy, which represents an acronym for Patients (P), Intervention (I), Comparison (C) and Outcomes (O-outcomes). Data collection took place in August 2021 in the databases of the National Library of Medicine and the Virtual Health Library (VHL). 14 articles were included in this review. As for the results, it was shown that the main benefits of pronation are: improving oxygenation and minimizing harmful ventilation; avoid the use and complications of neuromuscular blockade; improve arterial blood oxygen pressure and saturation level in patients, among others. Despite the presence of complications, such as pressure injuries, which were relatively common, pronation is associated with a reduction in mortality and its use is highly recommended, since complications are relatively minor compared to the benefits of this practice. However, in the protocol of this technique it is recommended that protection measures be adhered to. Therefore, it is up to the team to assess the best approach to treat and monitor clients who are using mechanical ventilation.